Problemy okresu okołooperacyjnego u chorych na dystrofię miotoniczną Steinerta, operowanych z powodu zaćmy - Zalewska, Renata; Mariak, Zofia; Markowska, Elżbieta; Czaban, Sławomir (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
Steinert's myotonic dystrophy is a genetically conditioned systemic disease with symptoms related to circulatory, respiratory, muscular, endocrine and mental disturbances. Most if not all of these patients develop lens opacification as a presenting symptom and need to undergo cataract surgery. Nevertheless, selection of a type of anaesthesia can arise to a problem in these patients because local anaesthesia can be insufficient whereas general endotracheal anaesthesia is known, to potentially provoke serious postoperative complications. In this contribution we discuss problems we faced during cataract surgery in three siblings affected by Steinert’s myotonic dystrophy. Two of them were operated on in local anaesthesia and developed intraoperative problems related to sudden increase of intraocular pressure, bleeding and vitreous efflux. After receiving a thorough examination the youngest of the three was operated on under short acting general intravenous anaesthesia (propofol and/or benzodiazepines, piperidine derived opioids, non-polarizing paralytics). We conclude that short acting general intravenous anaesthesia can help in avoiding both, local ocular complications during surgery and problems in the postoperative period.